Analysis of Babesia bovis infection-induced gene expression changes in larvae from the cattle tick, Rhipicephalus (Boophilus) microplus - Heekin, A.M.; Guerrero, F.D.; Bendele, K.G.; Saldivar, L.; Scoles, Glen A.; Gondro, C.; Nene, Vishvanath M.; Djikeng, Appolinaire; Brayton, K.A. (Springer, 2012)
Cattle babesiosis is a tick-borne disease of cattle that has severe economic impact on cattle producers throughout the world's tropical and subtropical countries. The most severe form of the disease is caused by the apicomplexan, Babesia bovis, and transmitted to cattle through the bite of infected cattle ticks of the genus Rhipicephalus, with the most prevalent species being Rhipicephalus (Boophilus) microplus. We studied the reaction of the R. microplus larval transcriptome in response to infection by B. bovis. Total RNA was isolated for both uninfected and Babesia bovis-infected larval samples. Subtracted libraries were prepared by subtracting the B. bovis-infected material with the uninfected material, thus enriching for expressed genes in the B. bovis-infected sample. Expressed sequence tags from the subtracted library were generated, assembled, and sequenced. To complement the subtracted library method, differential transcript expression between samples was also measured using custom high-density microarrays. The microarray probes were fabricated using oligonucleotides derived from the Bmi Gene Index database (Version 2). Array results were verified for three target genes by real-time PCR. Ticks were allowed to feed on a B. bovis-infected splenectomized calf and on an uninfected control calf. RNA was purified in duplicate from whole larvae and subtracted cDNA libraries were synthesized from Babesia-infected larval RNA, subtracting with the corresponding uninfected larval RNA. One thousand ESTs were sequenced from the larval library and the transcripts were annotated. We used a R. microplus microarray designed from a R. microplus gene index, BmiGI Version 2, to look for changes in gene expression that were associated with infection of R. microplus larvae. We found 24 transcripts were expressed at a statistically significant higher level in ticks feeding upon a B. bovis-infected calf contrasted to ticks feeding on an uninfected calf. Six transcripts were expressed at a statistically significant lower level in ticks feeding upon a B. bovis-infected calf contrasted to ticks feeding on an uninfected calf. Our experimental approaches yielded specific differential gene expression associated with the infection of R. microplus by B. bovis. Overall, an unexpectedly low number of transcripts were found to be differentially expressed in response to B. bovis infection. Although the BmiGI Version 2 gene index ( http://compbio.dfci.harvard.edu/tgi/cgi-bin/tgi/gimain.pl?gudb=b_microplus ) was a useful database to help assign putative function to some transcripts, a majority of the differentially expressed transcripts did not have annotation that was useful for assignment of function and specialized bioinformatic approaches were necessary to increase the information from these transcriptome experiments.